2014
DOI: 10.1016/s2215-0366(14)70312-8
|View full text |Cite
|
Sign up to set email alerts
|

Mental health interventions in schools in high-income countries

Abstract: Mental health services embedded within school systems can create a continuum of integrative care that improves both mental health and educational attainment for children. To strengthen this continuum, and for optimum child development, a reconfiguration of education and mental health systems to aid implementation of evidence-based practice might be needed. Integrative strategies that combine classroom-level and student-level interventions have much potential. A robust research agenda is needed that focuses on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
437
1
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 499 publications
(454 citation statements)
references
References 130 publications
(130 reference statements)
7
437
1
9
Order By: Relevance
“…Because of their readiness to learn, it needs relatively little guidance for them to progress. Seen by some as an optimum environment for the delivery of therapeutic work (Department for Education, 2011;Fazel, Hoagwood, Stephan & Ford, 2014), many schools now offer a range of interventions including counselling, play therapy, and arts therapies. Moore's (2011) Bristol Child and Adolescent Mental Health Services (CAMHS) Commissioners' evaluation of the local TaMHS Project described the collaborative working of art therapists and concluded that the interventions led to enhanced emotional wellbeing of the children involved, with noticeable improvements in social and academic areas.…”
Section: Mental Health In Schoolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of their readiness to learn, it needs relatively little guidance for them to progress. Seen by some as an optimum environment for the delivery of therapeutic work (Department for Education, 2011;Fazel, Hoagwood, Stephan & Ford, 2014), many schools now offer a range of interventions including counselling, play therapy, and arts therapies. Moore's (2011) Bristol Child and Adolescent Mental Health Services (CAMHS) Commissioners' evaluation of the local TaMHS Project described the collaborative working of art therapists and concluded that the interventions led to enhanced emotional wellbeing of the children involved, with noticeable improvements in social and academic areas.…”
Section: Mental Health In Schoolsmentioning
confidence: 99%
“…In accord with Fazel et al (2014) and Wengrower (2001) the school context was considered important by most parent participants. Delivering therapeutic interventions within an environment which has already been established as responsive and understanding may be key in providing the grounding for therapeutic engagement and seemed to offer containment for the teachers in their management of children's emotional needs.…”
Section: Change Reportedmentioning
confidence: 99%
“…It is noteworthy that no participants from the school that elected to use the program with a whole class indicated any stigma or concern about being selected. This has implications for school settings where the choice of a selective or universal intervention program (Fazel et al 2014) may inadvertently increase stigma and threaten the acceptability of the program for children. Komulainen (2007) identified the difficulty of working with children qualitatively such that their honesty can be skewed by the socialized context of the interview.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging health concerns include mental health problems, aggressive behaviour, bullying, obesity and type 2 diabetes (4). About 8% to 18% of school-aged children have been diagnosed with psychiatric disorders, and many more have undiagnosed emotional and behavioural problems (5). The most common psychiatric diagnoses are attention-deficit and hyperactivity disorder (ADHD) and anxiety disorders; however, oppositional disorders and depression are increasing (6).…”
Section: Le Pédiatre Et Les Pratiques Parentales Pendant La Phase Intmentioning
confidence: 99%